US wage determination system - Max J. Zenglein (Fachhochschule für Wirtschaft Berlin, IMB Institute of Management Berlin, 2007)
This paper analyses the wage determination mechanism in the United States taking legislative, economic and cultural factors into account. Unlike European countries the US system is dominated by an uncoordinated non-union wage system. The mechanisms as well as the development of this system are outlined in this paper. – – Dieser Aufsatz analysiert die Lohnfindungsmechanismen in den Vereinigten Staaten unter Berücksichtigung von legislativen, wirtschaftlichen und kulturellen Aspekten. Im Gegensatz zu vielen europäischen Ländern ist das US System nicht von Gewerkschaften geprägt. Die Mechanismen und Entwicklung dieses Systems werden in diesem Aufsatz beschreiben.
Keywords: 330